A novel medical device coating prevents Staphylococcus aureus biofilm formation on medical device surfaces. Issue 9 (16th May 2019) - Hogan, Siobhan; Kasotakis, Emmanouil; Maher, Sean; Cavanagh, Brenton; O'Gara, James P; Pandit, Abhay; Keyes, Tia E; Devocelle, Marc; O'Neill, Eoghan
ABSTRACT: Prevention of device related infections due to Staphylococcus aureus biofilms on devices represents a significant challenge. Such infections have recently been shown to be dependent on the coagulation pathway via activation of pro-thrombin and fibrin production. Three direct-thrombin inhibitors, argatroban, hirudin and dabigatran, were examined to determine their effect on preventing S. aureus biofilm on plastic biochip surfaces under shear stress using an in vivo relevant model of infection. Surface functionalization of polyurethane discs via dityrosine covalent crosslinking with hirudin was performed and changes in bacterial density and microscopic appearances determined. The three direct-thrombin inhibitors prevented S. aureus biofilm formation on plasma-coated surfaces treated with these agents. Coating of polyurethane with one of these agents, hirudin, significantly inhibited biofilm formation on the modified surface. These findings reveal the exciting potential for coating biomaterial surfaces with direct thrombin inhibitors to prevent staphylococcal binding and subsequent device-related infections. Abstract : Infections of implanted medical devices due to Staphylococcus aureus is a major problem. Here, we have identified the novel anti-staphylococcal biofilm potential of coating catheters with direct thrombin inhibitors.